Evaluation of Limb Length Discrepancy after Total Hip Replacement: A Teaching Hospital Based Study - Radha Krishna Choudhary (Asian Journal of Medical Research, 2019)
Background: Limb length discrepancy (LLD) or limb length inequality after Total hip arthroplasty (THA) is not an uncommon problem after THA and is associated with patient dissatisfaction, poorer outcome after THA and has been a common cause for litigation against orthopaedic surgeons. Subjects and Methods: Nineteen (19) Patients of age more than 25 yrs of either sex who have chronic symptoms of degenerative arthritis fitting inclusion criteria after excluding those who meet exclusion criteria are chosen among the outpatients at the Orthopaedic Department of WCMSRH, Jhajjar fulfilling the inclusion criteria. Results: In this study, postoperatively after THA, in 42.1% of cases, the limb to be operated were longer, in 10.5% of cases, the limb to be operated was shorter and in 47.4% postoperative limb length was equal as measured with absolute method and trochanteric method. Conclusion: All patients have good functional outcome after total hip replacement as functional score increases with time in subsequent follow up, irrespective of limb length discrepancy.